The Rate of Subsequent Surgery and Predictors Following ACL Reconstruction: Two- and Six-year Follow-up from a Multicenter Cohort - Hettrich, Carolyn M. (2013)
BACKGROUND: Subsequent surgeries have a profound impact on patient satisfaction and outcome following primary anterior cruciate ligament (ACL) reconstruction (ACLR). There have been no prospective studies to date describing the rate of all subsequent knee surgeries at short- and midterm follow-up along with analysis of surgical and patient variables that are associated with subsequent surgeries. PURPOSE: To report rate of all subsequent surgeries at short- and midterm follow-up, along with associated patient variables STUDY DESIGN: Prospective, Longitudinal Cohort METHODS: Nine hundred eighty patients (540 male) were prospectively enrolled in a multicenter cohort from January 2002 to December 2003. Two- and 6-year follow-up for subsequent procedures were obtained. Operative reports were obtained, and all procedures were recorded. RESULTS: One hundred eighty-five patients had a subsequent surgery on the ipsilateral leg (18.9%) and 100 on the contralateral knee (10.2%) at 6-year follow-up. On the ipsilateral knee, there was a 7.7% rate of ACL revisions, 13.3% rate of cartilage procedures, 5.4% rate of arthrofibrosis procedures, and 2.4% rate of procedures related to hardware. For the contralateral knee, there was a 6.4% rate of primary ACL ruptures. CONCLUSIONS: At 6-year follow-up 18.9% of ACLR patients underwent subsequent surgeries on the ipsilateral knee. The ipsilateral ACLR graft vs. contralateral normal ACL tear was similar (7.7% vs. 6.4%). Younger age at index surgery and the use of allograft were risk factors for subsequent surgery. Revision ACLR, female sex, body mass index (BMI), and surgical exposure were not significant.